Novel Coronavirus (SARS-CoV-2) resistance in African populations: A cause worth exploring: Novel coronavirus resistance in African population - Krishan, Kewal; Kanchan, Tanuj (Acta Biomedica Atenei Parmensis, 2020)
The pandemic caused by Novel Coronavirus SARS-CoV-2 shows its devastating effects all over the world. The American and the European countries are the worst-hit by this COVID-19 pandemic. However, most of the African countries excepting a few are less affected by this virus as far as the number of cases and deaths are concerned. The correspondence proposes that just like the abnormal haemoglobins HbS and HbC are found to provide immunity to the African populations against infectious diseases such as Plasmodium falciparum malaria The possibility of these abnormal haemoglobins offering certain protection against the Novel Coronavirus infection in these populations needs to be explored.